THE LEVEL UNDERSTANDING OF THERMODYNAMIC CONCEPT FOR PHYSICS AND CHEMISTRY UNDERGRADUATE STUDENTS - Dewi Wulandari; Destria Roza; M Aswin Rangkuti; Yul Ifda Tanjung; Irham Ramadhani (Jurnal Pendidikan Fisika, 2023)
Thermodynamics is an abstract concept making it difficult for physics and chemistry undergraduate student to understand it. The purpose of this research is to know the level understanding of the fundamental concepts of thermodynamics so that lecturers can develop strategies to teach thermodynamics appropriately. An exploratory small-scale study was conducted on students majoring in physics and chemistry to evaluate an understanding of heat, temperature, energy, work, thermodynamic processes and the first law of thermodynamics. The research sample consisted of 20 undergraduate students who were randomly selected from two majors, namely physics and chemistry. Data were collected through a diagnostic test to determine the level understanding of students' concepts which consisted of 20 questions. In addition, interviews were conducted with those of 20 students related to given questions. The results showed that the level of students' conceptual understanding of the concept of thermodynamics was still low. The main reasons that cause students have problems in understanding thermodynamic concepts are the concept of thermodynamics is an abstract physics concept and the matters of thermodynamics are lack in explanation and interpretation of phenomena and not linking them to daily life